Investigating the reinforcing mechanism and optimized dosage of pristine graphene for enhancing mechanical strengths of cementitious composites. Issue 70 (25th November 2020) - Ho, Van Dac; Ng, Ching-Tai; Ozbakkaloglu, Togay; Karunagaran, Ramesh U.; Farivar, Farzaneh; Goodwin, Andy; Guckin, Craig Mc; Ho, Van Duong; Losic, Dusan
Abstract : The proposed reinforcing mechanism and optimized dosage of pristine graphene (PRG) for enhancing mechanical, physicochemical and microstructural properties of cementitious mortar composites are presented. Abstract : The proposed reinforcing mechanism and optimized dosage of pristine graphene (PRG) for enhancing mechanical, physicochemical and microstructural properties of cementitious mortar composites are presented. Five concentrations of PRG and two particle sizes are explored in this study. The results confirmed that the strength of the mortars depends on the dosage of PRG. The PRG sizes have a significant influence on the enhancement rate of mechanical strengths of the mortars, whereas they do not have a significant influence on the optimized PRG dosage for mechanical strengths. The PRG dosage of 0.07% is identified as the optimized content of PRG for enhancing mechanical strengths. The reinforcing mechanism of PRG for cement-based composites is mostly attributed to adhesion friction forces between PRG sheets and cementitious gels, which highly depends on the surface area of PRG sheets. The larger surface area of PRG sheets has a larger friction area associated with cementitious gels suggested to be one of favorable parameters for enhancing mechanical strengths with graphene additives.